A Summary of Circular RNAs in Alzheimer's Disease - Xiao Rui; Wu Hong; Chen Keping (Journal of Neurological Research And Therapy, 2021)
Circular RNAs (circRNAs) are recently rediscovered eukaryotic molecules that form a covalently closed-loop structure through a special type of alternative splicing known as backsplicing. These closed-loop structures are highly stable and resistant to RNase degradation, and are thereby expressed in a tissue-specific and evolutionarily conserved manner, which regulates the expression of proteins and mRNAs that are involved in the metabolic pathways associated with specific diseases. Recent evidence of the ubiquitous expression of circRNAs in cancer under physiological and pathophysiological conditions indicates that dysregulation of gene and protein expression might promote tumorigenesis and carcinogenesis, and that circRNAs have important clinical significance in the diagnosis, treatment, and prognosis of cancer and other diseases. This review provides a brief introduction to the characteristics, formation, and function of circRNAs. Some of circRNAs act as microRNA (miRNA) sponges to regulate the level of transcriptional splicing and the expression of parental genes through the circRNA-miRNA-mRNA regulation axis. We summarize recent progress in above-mentioned circRNAs associated with Alzheimer's disease (AD).
Keywords: CircRNA